Disrupting discourses: the convergence of language, and cultural identity in Indian vernacular stand-up comedy - Farhan Ahmad; Anmolpreet Kaur; Sohaib Alam; Sameena Banu (Cogent Arts & Humanities)
Being a multifaceted nation, India is characterized by linguistic diversity, regional identities, and a vibrant tradition of political satire. The present study explores the emergence, evolution, and cultural and political implications of comedy that operates within local language and cultural contexts. It aims to analyse Indian vernacular stand-up comedy, and how it is used to highlight the native cultural absurdities and a tool of political resilience. The study underscores how growing standardisation has prompted Indian stand-up comics to opt for the vernacular modes. These vernacular voices establish a counter-hegemonic tradition by creating a more liberating landscape against institutional hierarchies of cultural and linguistic representation. By applying Foucault’s conceptual framework of power, discourse, and governmentality, this analysis unravels the intricate dynamics between power, control, discourse, and the subversive potential of humour. The study reveals that vernacular stand-up comedy as a creative expression of resilience advances critical discussion on language, culture, and identity.